A motion analysis in the volleyball spike - part 2: Coordination and performance variability - Serrien, B.; Ooijen, J.; Goossens, M.; Baeyens, J.-P. (International Journal of Human Movement and Sports Sciences, 2016)
Part one of this study described the three-dimensional kinematics of male and female top level and junior elite volleyball players during a spike. Different strategies for generating a high impact speed for the hand were observed between the groups. This part focuses on variability in coordination and performance and will use a single-subject approach for the data-analysis. The research question concerns the relationship between coordination variability and skill level. Two hypotheses exist about this relationship: a continuous decrease of variability or a U-shaped relationship when skill level increases. We used different measures of skill level during this study. The discrete measure (top level vs. junior elite) showed no difference in coordination variability. The continuous measures showed both U-shaped and linear relationships with coordination variability when data from all groups were pooled together. No relationships were observed within the groups. Together with the insight gained from the mechanical analysis from part one, knowledge about the coordination variability can be used for guiding the training and learning process of youth elite volleyball players.